INTEREST GROUP SESSION - RURAL AGING: VULNERABILITY AMONG OLDER ADULTS LIVING IN RURAL AREAS. (11th November 2018) - Hicken, B; Jackson, S L
Abstract: Over 10 million persons aged 65 and older live in rural areas of the United States (US). Aging frequently confers a host of challenges that increase vulnerability for abuse, exploitation, and neglect including: 1) worsening physical health; 2) declining cognitive abilities; 3) impaired functioning; 4) increased social isolation; and 5) dependence on others for support. The impact of these challenges may be exacerbated in the context of rural living where social supports and health care are limited and cultural factors may promote concealing of abusive situations. Thus, older adults in rural areas represent a group that may be especially vulnerable to abuse, exploitation, and neglect. This symposium will highlight various aspects of how aging in a rural community increases vulnerability to abusive or exploitative situations. The first three presentations review rural older adult populations in whom vulnerability may be especially concerning. The first presentation summarizes Department of Veterans Affairs (VA) data regarding vulnerability in older veterans and reviews several VA efforts to address elder abuse and intimate partner violence. The second presentation will report on health and emotional well-being outcomes of custodial caregiving in African-American grandparents living in rural areas. The third presentation will use rural Utah as a case example to illustrate the impact of opioid misuse in older adults on risk for overdose, injury, and exploitation. The final presentation will discuss strategies for leveraging limited community and individual resources to maximize intervention and prevention efforts for older adults living in rural areas who experience elder abuse.